Estimasi Model Persamaan Simultan Metode Two Stage Least Squares antara Sukuk dan Variabel Makro yang Mempengaruhi terhadap Pertumbuhan Ekonomi di Indonesia 2015-2021 - Dhani Masturoh; Anton Bawono; Musalim Ridlo (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
Abstract This study aims to test and analyze the relationship between Sukuk and macro variables that affect economic growth using the simultaneous model for the 2015-2021 period. This study uses secondary data types with a time series data model of Sukuk variables, macroeconomic variables consisting of inflation, poverty, exchange rates, interest rates, human development index (IPM), population size, and economic growth (GDP) in Indonesia. Furthermore, the data were tested using multiple linear regression models and simultaneous model tests, to obtain test results and complex analysis of exogenous and endogenous variables and their effect on economic development, with the help of the EVIEWS version 9 application. The results of this study indicate that Sukuk has a positive and significant effect on economic growth. Simultaneously, Sukuk is affected by the exchange rate, which has a negative and significant effect, and inflation, which has a positive and significant effect. Inflation has a positive but not significant effect on economic growth. Simultaneously inflation is influenced by the exchange rate which has a positive and significant effect and is influenced by interest rates which have a negative but not significant effect. poverty has a positive and significant effect on economic growth. Simultaneously, poverty is affected by inflation, which has no significant negative effect, HDI, which has a significant negative effect, and the number of inhabitants, which has a significant negative effect. Keywords: sukuk, inflation, poverty, exchange rates, interest rates, human development index (IPM), population, and economic growth (GDP).